Gastrointestinal angiodysplasia and bleeding in von Willebrand disease - Franchini, Massimo; Mannucci, Pier Mannuccio (Thrombosis and Haemostasis, 2014)
Von Willebrand disease (VWD), the most common genetic bleeding disorder, is characterised by a quantitative or qualitative defect of von Willebrand factor (VWF). Patients with VWD suffer from mucocutaneous bleeding, of severity usually proportional to the degree of VWF defect. In particular, gastrointestinal bleeding associated with angiodysplasia is often a severe symptom of difficult management. This review focuses on the pathophysiology, diagnosis and treatment of VWD-associated gastrointestinal angiodysplasia and related bleeding.
Keywords: von Willebrand disease; bleeding; gastrointestinal angiodysplasia; therapy